Diagnostic spectrum of CSF involvement by malignant cells: three-year experience of tertiary care hospital in CSF cytology - Rana, Vandana; Sidhu, Avnit; Jagani, Rajat; Singh, Giriraj; Singh, Rajeshwar; Rathi, K. R. (International Journal of Research in Medical Sciences, 2017)
Background: Cerebrospinal fluid (CSF) cytology is the diagnostic gold standard test for primary or metastatic involvement of central nervous system (CNS) by malignancy. It is a very important and routinely done test in the laboratory but its sensitivity is low due to many confounding factors and varies amongst type of malignancies. We did retrospective analysis of CSF cytology carried out at our center from January 2013 to December 2015 to find out about spectrum of malignancies being detected on CSF cytology. Methods: From January 2013 to December 2015, three hundred and seventy-five CSF samples were received and processed for presence of malignant cells at our center. The cytospin preparations stained with LG and PAP stains of these CSF samples were analyzed along with any special stain that was available in the records. Clinical details of the patients with positive cytology were correlated from records. Results: The diagnostic spectrum obtained through study of positive CSF cytology included cases of metastatic solid malignancies and hematolymphoid malignancies. Four cases out of ten were of Metastatic Adenocarcinoma with primary origin being Breast, Lung and Stomach. Out of six cases of hematolymphoid malignancies; five were known cases of lymphoma/leukemia and one was primarily diagnosed to have Non-Hodgkin’s lymphoma (NHL) on CSF cytology. Conclusions: Both Epithelial and Hematolymphoid malignancies can be diagnosed on CSF cytology and these are predominantly metastatic in origin; Hematolymphoid malignancies are more common in CSF than solid malignancies. Correlation with clinical details and Neuroimaging is a must.